2005
DOI: 10.1086/428025
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use, Human Capital, and Wages

Abstract: Abstract:This article develops and estimates a model of wage determination that isolates the effects of alcohol use on wages as mediated through human capital accumulation. Although generally insignificant, estimation results suggest that moderate alcohol use while in school or working has a positive effect on the returns to education or experience, and therefore on human capital accumulation, but heavier drinking reduces this gain slightly. Based on these results, alcohol use does not appear to adversely affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 33 publications
3
55
0
Order By: Relevance
“…However, epidemiological studies have found that the incidence of miscarriages is also higher due to the consumption of cigarettes and alcohol during pregnancy (Kline et al 1980). At the same time, smoking cigarettes and drinking alcohol are correlated with labor market outcomes (Bray 2005;Johansson et al 2007;Levine et al 1997). This undermines the internal validity of the instrument based on miscarriage data.…”
Section: Analytical Strategymentioning
confidence: 99%
“…However, epidemiological studies have found that the incidence of miscarriages is also higher due to the consumption of cigarettes and alcohol during pregnancy (Kline et al 1980). At the same time, smoking cigarettes and drinking alcohol are correlated with labor market outcomes (Bray 2005;Johansson et al 2007;Levine et al 1997). This undermines the internal validity of the instrument based on miscarriage data.…”
Section: Analytical Strategymentioning
confidence: 99%
“…While most prior work on the relationship between intoxicants and labor market outcomes has focused on alcohol or illegal drug use, the relationship between prescription opioids and labor market outcomes may fundamentally differ from that of alcohol or illicit drugs (Cook and Moore, 1993;French and Zarkin, 1995;Sindelar, 1993, 1996;Buchmueller and Zuvekas, 1998;Zarkin et al, 1998;DeSimone, 2002;Auld, 2005;Bray, 2005). The aforementioned therapeutic potential implies that prescription opioids may positively affect employment outcomes in moderation, but negatively affect employment when taken for illegitimate purposes or in excess.…”
Section: Introductionmentioning
confidence: 99%
“…Wage losses due to smoking are reported by Auld (2005), who estimated a system of equations and found wage gains for drinkers. The work of Bray (2005) is the first that explicitly models the mechanism through which drinking affects wages, namely through the formation of human capital. The empirical application of his theoretically derived model suggests that moderate alcohol consumption exerts positive effects on the returns to education and experience, whereas heavy drinking has a negative impact.…”
Section: Background and Previous Studiesmentioning
confidence: 99%